CSR and financial performance parameters of DBBL: An empirical analysis - Farijul, Islam; Rahman, Mostafizur (International Journal of Innovation and Scientific Research, 2016)
The purpose of the current study is to show the statistical linkage between CSR expenditure of financial service firm mainly DBBL and its financial performance on the basis of some key parameters that attempts to contribute to the existing knowledge of corporate social responsibility initiatives by businesses and its ability to influence their financial performance. Consequently, the main objective is to examine the relationship between CSR and financial performance of the banking sector. For this purpose, various financial drivers are used such as EPS, DPS, NPAT, ROE, EVA ROA, MVA and, ROE and ROI. After getting all the relevant data from secondary sources like annual reports and reports from Bangladesh Bank, statistical tool like multivariate analysis in the form of Bi-variate Regression is used to depict the relationship and the developed hypotheses are tested by using Univariate analysis in the form of one sample t test under parametric test. The major finding of this study demonstrates evidence that there is a statistical significant linkage between CSR and Performance of the sample bank.
Keywords: CSR; DBBL; Financial performance parameters